Devotion and resistance: the tactics of the Folia de Reis Hosts in the metropolitan region of the State of Rio de Janeiro - Souza, Luiz Gustavo Mendel (Revista de Antropologia, 2020)
The Folias de Reis organize visits to the homes of the devotees in a period known as giros or journeys, taking place at dawn on weekends between December 24 and January 6, the day of the Santos Reis. In order to carry out an ethnographic study that encompasses the complexity of this devotional endeavor, this article is divided into three parts: a first part that discusses who are the devotees of the Folia de Reis and their roles in the execution of devotion, a second part explores the availability of the spaces of home and street at the time of the revelry tours, and the final part of exploring the “tactics” (CERTEAU, 1994) practiced by the devout hosts of the flag to guarantee the physical and moral integrity of the revelers and their families during the ritual circuit carried out on the periphery of the Metropolitan Region of the State of Rio de Janeiro.